Community mediation in Malaysia: Training and accreditation of mediators in comparison with SCMC and IIAM - Ambaras Khan, Mushera Bibi; Abdul Hak, Nora (2016)
Community mediation in Malaysia is a programme created by the Department of National Unity and Integration (DNUI) in providing an alternative dispute resolution method to the citizens at the community level, as to enable them to resolve disputes amicably. Formal mediation requires the mediators to have a standard practice. Therefore, an institution that is offering mediation services to the people is encouraged to provide proper training and accreditation to the mediators. Accreditation usually occurs in the context of organisational schemes designed to promote quality, standards and accountability among practitioners. Accreditation can be advantageous as it will set a benchmark standard, inspires public confidence and it is consistent with the movement towards the introduction of the reliable public standard. The objective of this paper is to study the practice in Singapore and Kerala, India to be compared with the practice in Malaysia. The authors adopted library based and empirical legal research i.e., a qualitative method in collecting data. From the data collected, it is found that in Singapore, the community mediators are accredited by the Singapore Community Mediation Centre (SCMC) and in Kerala, India the community mediators are appointed and accredited by IIAM (Indian Institute of Arbitration and Mediation‖). However, in Malaysia, the community mediators are trained by the Institut Kajian dan Latihan Integrasi Nasional (IKLIN) (National Integration Research and Training Institute), DNUI but is yet to be accredited by a specific body that acquires a national or intentional standard. Therefore, it is suggested for the DNUI to adopt a standard that would allow the community mediators in Malaysia to be accredited and accepted at the national and international level.